2017
DOI: 10.5578/tcb.2017.002
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry and Flow-Volume Curve

Abstract: Spirometry is the essential part of a pulmonary function study and provides the most information. The two most important dynamic lung volumes measured are the forced vital capacity (FVC), and the forced expiratory volume in the 1st second (FEV 1 ). The third important parameter FEV 1 /FVC ratio is used to differantiate obstructive from restrictive lung disorder. The flow-volume curve is more informative and easier to interpret, as different disease produce distinct curve shapes. In this review spirometry and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…FEV1/FVC% (%) value is an important parameter used in identifying restrictive lung diseases like respiratory insufficiencies and the occlusion in airways found in lungs (Demir, 2017). In our study findings, it has not been found that there is statistically significant difference in FEV1/FVC% (%) value according to smoking addiction and exercise variables among the groups (p>0,05).…”
Section: Discussioncontrasting
confidence: 56%
“…FEV1/FVC% (%) value is an important parameter used in identifying restrictive lung diseases like respiratory insufficiencies and the occlusion in airways found in lungs (Demir, 2017). In our study findings, it has not been found that there is statistically significant difference in FEV1/FVC% (%) value according to smoking addiction and exercise variables among the groups (p>0,05).…”
Section: Discussioncontrasting
confidence: 56%
“…FVC is the volume of air exhaled from the lung by maximal expiration after deep inspiration (Miller et al, 2005). FVC values are reduced in the presence of obstruction or restriction (Demir, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…• FVC is the volume of air exhaled from the lung by maximal expiration after deep inspiration (Miller et al, 2005). FVC values are reduced in the presence of obstruction or restriction (Demir, 2017). • FEV 1 refers to the volume of air extracted during the first second of forced expiration after full inspiration.…”
Section: Data Collectionmentioning
confidence: 99%
“…Lung function tests are used to measure lung volumes and capacities and to monitor respiratory muscles, ways of breathing and expansion capacity of lung (Kayatekin at al., 1993) The main object of the pulmonary function tests is the spirometry, which introduces very important data. Forced vital capacity (FVC) and forced expiratory volume in one second (FEV1) are the two most important parameters assessed in a spirometry testing (Demir, 2017). Another parameter assessed by spirometry is the Peak Expiratory Flow (PEF) level.…”
Section: Introductionmentioning
confidence: 99%